(untitled) (Journal of Psychiatrists’ Association of Nepal, 2022)
Introduction: Though there are studies in the past done to assess the prevalence of tobacco use in the country, little is known about the state of nicotine dependence among tobacco users and the co-occurrence of nicotine dependence and psychiatric disorders in Nepal. Objectives: To estimate the prevalence of tobacco use, the level of nicotine dependence among the users and the psychiatric disorder-specific prevalence among tobacco users in a community settng. Methodology A cross-sectional study was conducted in the community of Dharan. One hundred twenty-eight cases (size) were enrolled from different wards of Dharan using the Population proportionate random sampling technique. The Fagerström Test for Nicotine Dependence (FTND) was applied to assess the level of nicotine dependence and the Mini International Neuropsychiatric Interview (M.I.N.I.) was for the diagnosis of Psychiatric disorders. Result: The prevalence of tobacco use was 41.4%. Tobacco use was more common among males and those with a family history of tobacco use and psychiatric illness (p-value< 0.05). The smoking form was more common than smokeless one. Most tobacco users had moderate nicotine dependence and started the use in their 20s. Among tobacco users, 23 cases had comorbid psychiatric diagnoses, common being alcohol and other substance, depression and anxiety disorders. Conclusion: The prevalence of tobacco use was high in the community. Young persons in their 20s should be given special attention while conducting educational and awareness programs regarding tobacco prevention. Psychiatric comorbidities should be assessed routinely among tobacco users.